Frequency-risk and duration-risk relationships between aspirin use and gastric cancer: a systematic review and meta-analysis. - Xiaohua Ye; Jinjian Fu; Yi Yang; Yanhui Gao; Li Liu; Sidong Chen (PLoS ONE)
Background Although previous meta-analyses have suggested an association between aspirin use and risk of gastric cancer, current evidence is inconsistent. Additionally, it remains unclear whether there are frequency-risk and duration-risk relationships and if a threshold of effect exists. Methods We identified studies by searching MEDLINE and PUBMED databases and reviewing relevant articles. We derived the summary risk estimates using fixed-effects or random-effects model based on homogeneity analysis. The dose-response meta-analysis was performed by linear trend regression and restricted cubic spline regression. Potential heterogeneity was tested using the Q statistic and quantified with the I (2) statistic. Subgroup analyses and Galbraith plots were used to explore the potential sources of heterogeneity. Publication bias was evaluated with funnel plots and quantified by the Begg's and Egger's test. Results Fifteen studies were included in this meta-analysis. There was an overall 29% reduced risk of gastric cancer corresponding to aspirin use (RR  = 0.71, 95% CI 0.60-0.82). We found there are nonlinear frequency-risk and linear duration-risk relations between aspirin use and gastric cancer. A monotonically decreasing relation was observed only for low-frequency (≤4.5 times/week) aspirin intake (10% decreased risk for once/week, 19% for twice/week and 29% for 4.5 times/week), and the frequency threshold of aspirin use is 4.5 times per week. Regarding those with duration of aspirin use, there was a tendency towards stronger risk reduction of gastric cancer for longer aspirin use (10% decreased risk for 4 years, 19% for 8 years and 28% for 12 years), and no duration threshold was observed. Conclusion Our findings suggest that long-term (≥4 years) and low-frequency (1-4.5 times per week) aspirin use is associated with a statistically significant, dose-dependent reduction in the risk of gastric cancer.